STRATEGI PENGEMBANGAN PRODUKSI KAKAO (Theobroma cacao) (Studi Kasus Kelompok Wanita Tani Pawon Gendis) - Ayyub, Ahmad; Harli, Nurlina (Fakultas Pertanian, Universitas Janabadra, 2023)
This study aims to analyze the challenges faced by the Pawon Gendis Farmer Women group by identifying internal and external factors that affect it. The results of this analysis will be used to formulate an optimal development strategy. Data was collected through field surveys, interviews with group managers, employees, and consumers using Google Forms, and involved documentation. The results of the IFAS analysis showed a score of 3.12 for strengths and weaknesses. While the EFAS results show a score of 3.78 for opportunities and threats. By compiling a SWOT Matrix based on a combination of strengths-opportunities, strengths-threats, weaknesses-opportunities, and weaknesses- threats, it is expected to formulate an appropriate strategy. The proposed alternative strategy is an aggressive strategy, focusing on harnessing power to improve product image and control tofu prices in the face of soybean price fluctuations. The goal is to increase competitiveness and attract more consumers, which will ultimately provide significant benefits to the Pawon Gendis Farmer Women group. Keywords: development strategy, IFAS, EFAS, KWT Pawon Gendis INTISARIPenelitian ini bertujuan untuk menganalisis tantangan yang dihadapi oleh Kelompok Wanita Tani (KWT) Pawon Gendis dengan mengidentifikasi faktor internal dan eksternal yang memengaruhinya. Hasil analisis ini akan digunakan untuk merumuskan strategi pengembangan yang optimal. Data dikumpulkan melalui survei lapangan, wawancara dengan pengelola kelompok, karyawan, dan konsumen menggunakan Google Form, serta melibatkan dokumentasi. Hasil analisis IFAS menunjukkan skor 3,12 untuk kekuatan dan kelemahan. Sementara hasil EFAS menunjukkan skor 3,78 untuk peluang dan ancaman. Dengan menyusun Matriks SWOT berdasarkan kombinasi kekuatan- peluang, kekuatan-ancaman, kelemahan-peluang, dan kelemahan-ancaman, diharapkan dapat merumuskan strategi yang sesuai. Strategi alternatif yang diusulkan adalah strategi agresif, dengan fokus pada memanfaatkan kekuatan untuk meningkatkan citra produk dan mengendalikan harga tahu dalam menghadapi fluktuasi harga kedelai. Tujuannya adalah meningkatkan daya saing dan menarik lebih banyak konsumen, yang pada akhirnya akan memberikan manfaat signifikan bagi KWT Pawon Gendis. Kata kunci : strategi pengembangan, IFAS, EFAS, KWT Pawon Gendis